The Role of Dynamic Capabilities in the context of Change: The Case of Health Units in the Region of Lisbon and Vale Do Tejo, Portugal - Ruben LOUREIRO; Jorge SIMÕES; Silvio SILVA; Carlos QUEIROZ; Carolina MARTINS (Communications of International Proceedings, 2021)
The objective of this research is to identify how the Dynamic Capabilities existing in hospitals belonging to the Region of Lisbon and Vale do Tejo (RLVT), influence and contribute to improve their performance, in the face of a new reality imposed by the environment. For this, six interviews were carried out with the chief nurses of the RLVT. According to the results obtained, it appears that hospitals were not prepared to face the pandemic, however, after some learning and the assimilation of relevant information, health professionals, together with the available resources, were able to adapt to the new situation and innovate in the provision of adequate health care, thus concluding that the development and implementation of Dynamic Capabilities, positively influence the performance of health institutions.
Keywords: Dynamic Capabilities; health institutions; performance; resources; pandemic.